Indicator‐based natural capital reporting to inform decision‐making in the Brazilian Pantanal - Alison J. Fairbrass; Victor Moretti; Elvander Quaresma; Celma Ribeiro; Fabio deOliveira Roque; Claudio Oller; Julia Tomei (Conservation Science and Practice, 2025)
Abstract The natural capital indicator framework (NCIF) offers an entry‐level approach to natural capital reporting using existing data sources and indicators. Here, we test the NCIF for the first time in the megadiverse Pantanal biome in Brazil. We compile publicly available indicators on the cattle, soy, fishing, and nature‐based tourism industries alongside indicators on the state of the biome and its ecosystem services. We show that the NCIF is quick to implement using existing environmental and socioeconomic indicators produced by public and NGO statistics communities. However, we identify significant gaps in indicators on the condition and economic value of the biome, the human investment required to derive benefits from the biome, emissions produced by the industries that exploit the biome, and the ecosystem services that maintain the functioning of the biome, such as nutrient cycling and biodiversity. Existing initiatives in Brazil could fill natural capital reporting gaps, including Brazil's experimental natural capital accounts. The NCIF provides a structured approach to highlight gaps in natural capital reporting and guide decision‐makers to prioritize investment in filling data and reporting gaps. Systematic, transnational monitoring must fill gaps in natural capital data to inform decision‐making in the megadiverse Pantanal biome.